"I Don't Want to Grow Up and Not be Smart": Urban Indigenous Young People's Perceptions of School. Issue 1 (22nd July 2010) - Nelson, Alison; Hay, Peter J.
Abstract: In light of the policy and research interests in optimising the educational experiences and outcomes of Indigenous young people, this paper aims to give voice to young Indigenous students' experiences of school and to convey a sense of the varied and complex nature of their educational and life pathways. Using a qualitative, life history research approach, 14 young people were interviewed seven times over two and a half years as they transitioned from primary school to secondary school in order to explore their perceptions of health, schooling and plans for the future. The findings demonstrate the complex and multifarious lived experiences of these young people and the incongruence with apparent assumptions underpinning education policies focused on improving and measuring educational outcomes. We argue that in order to avoid isolating, threatening or marginalising Indigenous (or any other) students within education systems, traditional educational pathways and trajectories need to be challenged so as to celebrate the cultural wealth of young people; recognise, value and build on their previous educational experiences; and support the transition across different learning and vocational avenues.